Pola Jaringan Sosial Waria di Kabupaten Empat Lawang - Iklan Sandora, Iklan Sandora; Diana Dewi Sartika, Diana; Andy Alfatih, Andy Alfatih; Isyanawulan, Gita; Putra, Decka Pratama Putra; Ifaty (Rumah Jurnal, University of Jember, 2025)
This study's main topic is the discussion of transgender social networks in Empat Lawang Regency's Pendopo District. The phrase